Kegiatan Ekstrakurikuler Drum Band di SMA N 1 Batusangkar - Arif Rahman , Arif Rahman; Harisnal Hadi (EDUMUSIKA, 2024)
This study aims to describe the extracurricular activities of the drum band at SMA N 1 Batusangkar. The type of research is qualitative research using descriptive methods. Data collection techniques are carried out through literature studies, interviews, observations, and documentation, data analysis techniques are collecting data, clarifying data and concluding data. The results of this study show that the results of drumand extracurricular activities at SMA N 1 Batusangkar are running well. Drumband extracurricular activities at SMA N 1 Batusangkar were carried out 17 times. Drumband extracurricular activities at SMA N 1 Batusangkar have several important stages, ranging from planning to evaluation. This study examines the implementation of Drumband extracurricular activities, with a focus on the selection, training, and evaluation of members as well as the management of musical instruments. The results of the research concluded that the activity ran smoothly thanks to the support of coaches and coaches. Various training methods, such as the observation method, demonstration method, individual training method, group training method and combined training method are important factors in maintaining the smooth running of the activity. Despite facing several obstacles, such as student discipline and the accuracy of notes in playing music, the efforts made by coaches and coaches were able to overcome them. The implication of this study is the importance of paying attention to these activities to ensure the smooth running and for students involved in Drumband activities.